FAKTOR RISIKO KANKER PAYUDARA - Alyatul Aulia; Aldha Dwi Febrima; Meta Zulyati Oktora (Nusantara Hasana Journal, 2024)
Breast cancer originates from malignant cells in the breast glands, ducts, and supporting tissues. According to the National Breast Cancer Foundation, various risk factors contribute to breast cancer, including genetic factors, family history, age, breastfeeding status, early age at menarche, age at menopause, parity, use of hormonal contraception, smoking, alcohol consumption, frequency of physical activity, excess weight after menopause, and chest radiation exposure. Data from the International Agency for Research on Cancer (IARC) indicate that in Asia, common risk factors for breast cancer include alcohol consumption, radiation exposure, diet, nutrition, excess body weight, physical activity, genetic factors, as well as reproductive and hormonal factors. This study aims to identify the risk factors associated with breast cancer in women. Methods of this study is a systematic literature review with a deductive approach, following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. The search strategy utilized the PICO framework (Population, Intervention, Comparison, and Outcome). Relevant journals were sourced from online databases such as PubMed, Google Scholar, and DOAJ, covering publications from 2019 to 2023. From the search of online databases like PubMed, Google Scholar, and DOAJ, 10 full-text journals met the inclusion criteria and focused on discussing the risk factors for breast cancer. Several risk factors are associated with breast cancer. Among these, the use of hormonal contraception and a family history of breast cancer have a significant relationship with the incidence of the disease.